Infiltrasi Hermeneutika ke Matan Hadis - Ramadani, M Rizko; Urrahmi, Syifa (Journal of Hadith Studies, 2020)
Hadiths are an authoritative source of Islamic teachings, yet their interpretations are often textual and neglect historical or social contexts. This phenomenon has resulted in authoritarian and even misogynistic interpretations that marginalize certain groups, especially women. This article seeks to answer three main questions: how the hermeneutic approach is applied in understanding hadith texts, what factors influence its use, and what goals it aims to achieve. This research employs a library study method with a descriptive-analytic approach. Data were obtained from the works of Khaled Abou El Fadl and other hermeneutic literature on hadith. The findings reveal that the hermeneutic approach, particularly Khaled's negotiation-based hermeneutics, offers a more contextual and open model of interpretation through three core elements: author, text, and reader. This method avoids interpretive authoritarianism and opens space for adaptive ijtihad in responding to contemporary realities. Therefore, hermeneutics serves as a crucial tool for revitalizing hadith understanding to maintain its relevance and authenticity in an evolving modern world.